Bydlení v „pečovatelských bytech“ z pohledu nabídky a očekávání - Leznar, Zdeněk (Univerzita Pardubice, 2012)
Social policy has defined its scope. Some, such as social services, more attention is paid, some are more neglected. These include the area of housing policy, particularly social housing. This is an area that is left more or less the powers of municipalities and local governments. One of the types of social housing is apartments for the elderly and disabled. It is then a question of what motivated these people come asking for such an apartment, the extent to which their claim is justified.
Living in "nursing homes" from the perspective of supply and expectations
Keywords: social services; nursing homes; social housing; motivation; home care